Pengaruh Mixed Bundled Products dan Keragaman Produk terhadap Keputusan Pembelian Konsumen Mak–Mak di Yogyakarta - Ardika Irfanto; Fitri Wahyuningtyas, Yunita (Politeknik Negeri Jakarta, 2025)
This study aims to analyze the effect of mixed bundled products and product diversity on consumer purchasing decisions on Indomie products in Yogyakarta. This study uses two independent variables, namely mixed bundled products (X1), and product diversity (X2), and one dependent variable, namely purchasing decisions (Y). Data were collected through questionnaires distributed to respondents who attended the Indofood event in Yogyakarta. Data analysis using multiple linear regression, validity test, reliability test, and classical assumption test. The results showed that mixed bundled products had no significant effect on purchasing decisions. This is due to the lack of consumer interest in bundled products, even though the price offered is attractive. In contrast, product diversity has a significant positive effect on purchasing decisions, where the more product variations offered, the more likely consumers are to buy. This study suggests that companies pay attention to consumer preferences in compiling bundled packages and increase product diversity in order to fulfill consumer desires. This study has limitations in the aspect of location, namely Yogyakarta and the focus of the variables studied.